Introducing methadone maintenance therapy into Ukrainian prisons: a qualitative study of criminal subculture, Russia’s full-scale invasion, and contested methadone objects - Ponticiello, Matthew; Azbel, Lyu; Tate, Mary M.; Bromberg, Daniel J.; Pykalo, Iryna; Kiriazova, Tetiana; Saichuk, Natalya; Altice, Frederick L. (Frontiers in Psychiatry, 2023)
Methadone was newly introduced into Ukrainian prisons in 2021 as part of a national scale-up strategy to treat opioid use disorder and prevent transmission of HIV and HCV infections. Opioid agonist therapy (OAT) scale-up in Eastern Europe and Central Asia has been hampered by varying levels of influence of criminal subculture. This study examined the socio-environmental factors influencing the uptake of methadone treatment in Ukrainian prisons, including changes that evolved during Russia's full-scale invasion of Ukraine and displacement of people deprived of liberty (PDL) from conflict to non-conflict regions. In-depth qualitative interviews (N=37) were conducted from January 2021 to October 2022 in the only two Ukrainian prisons where methadone was being introduced with PDL (N=18) and continued to provide it after the full-scale invasion, former PDL (N=4), and prison staff (N=15). Interviews were audio-recorded, transcribed and translated into English. Four authors independently reviewed, coded, and applied a phenomenological framework for data analysis. Criminal subculture perceptions varied, with some seeing it as strongly discouraging drug use among certain groups, while others described it as a weak influence from the past. The subculture's influence on methadone treatment uptake, however, was less clear. PDL and prison staff struggled to identify and articulate differences between illicit street-bought methadone, used recreationally, and medically prescribed methadone. Thus, the meaning of "methadone" varies in its interpretation as it is being introduced, making it potentially conflicting for patients to opt into this evidence-based treatment. As Russia invaded Ukraine in 2022, PDL from conflict zones were transferred to non-conflict regions where methadone was being introduced. The prison environment became more enabling for PDL to start methadone as they were segregated and not subject to the existing criminal subculture's rules and lacked social ties necessary to procure drugs illegally. Criminal subculture is evolving in Ukrainian prisons, and appears to be impacted by the Russian invasion. As methadone scale-up in prisons expands, it will be important to distinguish the meaning of methadone perpetuated by the prison subculture versus its intended meaning as a medical treatment by the formal prison authorities. The current invasion of Ukraine by Russia may disrupt this course.